Evaluation of Design Efficiency using Boothroyd Dewhurst Method for PCB Drilling Machine Products - Aqmal Idham, Abdul Shukor; Asrul, Adam (United Kingdom Simulation Society, 2018)
This paper presents the investigation on design efficiency of two different 3-axis printed circuit board (PCB) drilling machine products using Boothroyd Dewhurst design for manufacturing and assembly (DFMA) approach. The two products that are used as a case study named machine A and machine B products. The investigation also intends to analyze on the total operation time, and total parts of the two existing machine products. A comparative study was done for both products that give better results for machine A in term of design efficiency and total operation time compared to machine B. However, the total parts of machine A is still higher than machine B. Therefore, the modified machine A is proposed to improve the design efficiency by minimizing the total parts of machine A. The Boothroyd Dewhurst DFMA technique is then utilizedd to analyze the proposed modified machine A. As results, the design efficiency of the proposed modified machine A improves from 5.81% to 9.24%.